Peran Profesi Akuntan Dalam Meningkatkan Ketahanan Keuangan Di Era VUCA (Analisis Bibliometrik) - Nabila, Bilqist; Yuhertiana, Indrawati (Akmenika: Jurnal Akuntansi dan Manajemen, 2025)
This study aims to analyze the development of publications, trends, and dynamics related to the topic of the Accounting Profession and Financial Resilience in the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) Era from 2020 to 2024. Additionally, it seeks to identify the scientific articles with the highest number of publications on this topic. Data was collected using the Publish or Perish application with the Google Scholar database. The implemented criteria included article titles, abstracts, and keywords within the 2020-2024 timeframe. The search process yielded 200 articles, which were then processed using VOSviewer software, resulting in 85 articles relevant to the topic of the Accounting Profession and Financial Resilience in the VUCA Era. Furthermore, through variable selection in VOSviewer, 24 variables were identified that relate to the role of the accounting profession in financial resilience in facing the VUCA era. This study highlights the positive development of publications on this topic, making it an interesting subject for further research.